2017
DOI: 10.3389/fpls.2017.00578
|View full text |Cite
|
Sign up to set email alerts
|

Elevation Shift in Abies Mill. (Pinaceae) of Subtropical and Temperate China and Vietnam—Corroborative Evidence from Cytoplasmic DNA and Ecological Niche Modeling

Abstract: The “elevational shift” scenario has been proposed as a model to explain the response of cold-adapted organisms to Quaternary climatic fluctuations in Europe and North America. However, the elevational shift model has not been well-explored in eastern Asia, which is more topographically complex than the other Northern Hemisphere biogeographic regions. Here, we evaluated the role of elevational shift in the closely related firs, or Abies Mill., of subtropical and temperate China. These firs are typical alpine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 92 publications
1
20
1
1
Order By: Relevance
“…Compared with other full‐migration projections, our optimistic forecast for A. recurvata was not consistent with the overall declining trend of the genus Abies as highlighted by Liu et al () and Shao et al (). Benefiting from future climate change, a large number of currently unoccupied areas in southern and western Sichuan will be potentially suitable for A. recurvata (Figure a).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Compared with other full‐migration projections, our optimistic forecast for A. recurvata was not consistent with the overall declining trend of the genus Abies as highlighted by Liu et al () and Shao et al (). Benefiting from future climate change, a large number of currently unoccupied areas in southern and western Sichuan will be potentially suitable for A. recurvata (Figure a).…”
Section: Discussioncontrasting
confidence: 97%
“…Full migration trend of the genus Abies as highlighted by Liu et al (2018) andShao et al (2017). Benefiting from future climate change, a large number of currently unoccupied areas in southern and western Sichuan will be potentially suitable for A. recurvata (Figure 4a).…”
Section: Partial Migrationmentioning
confidence: 99%
“…While the taxonomic limits of the Abies genus are well known at the species‐ and infraspecific‐levels (Aguirre‐Planter et al, ; Vázquez‐García et al, ; Wang et al, ; Cinget et al, ; Shao et al, , ), its infrageneric classification remains unsettled (Liu, ; Farjon & Rushforth, ; Eckenwalder, ; Farjon, ). Most prior infrageneric classifications of Abies have either been restricted to particular geographic areas, such as North America, Japan, east Asia (e.g., Engelmann, ; Mayr, ; Patschke, ), or were based on a small number of morphological characters (e.g., Hickel, ‐08; Patschke, ; Landry, ).…”
Section: Introductionmentioning
confidence: 99%
“…forrestii ) is considered as near‐threatened (Zhang, Katsuki, & Rushforth, ). Studies have suggested the taxonomic boundaries are well‐established at the species and intraspecific levels of the Abies genus (e.g., Aguirre‐Planter et al, ; Cinget, Lafontaine, Gérardi, & Bousquet, ; Shao & Xiang, ; Shao et al, ; Wang, Abbott, Ingvarsson, & Liu, ); however, their intrageneric classification is an active area of research (Eckenwalder, ; Farjon, ). These four taxa selected for study vary in their morphological traits and have dissimilar environmental requirements, according to information from other studies (e.g., China Forest Editorial Board, ; Guan & Zhou, ; Shao et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge of Quaternary refuge distributions of species long ago (Cao et al, ), as well as remaining refuge distributions under current climate change conditions (Tinner & Valsecchi, ), can inform the future protection of Abies trees against climate change. Several studies have addressed the biogeographic history of Abies species in the TP (e.g., Peng et al, ; Shao, Zhang, Phan, & Xiang, ; Xiang et al, ), but a thorough understanding of it still eludes us. This may be due, in part, to the lack of using integrative approaches that incorporate both palynological and phylogeographical data.…”
Section: Introductionmentioning
confidence: 99%